AIRPORTS AND THE ENVIRONMENT - Vodolaskova, Kateryna Yu. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: the idea of sustainability in environment elevates by ground handling of airports are highlighted and the importance of governance policy of development planning of national airports in accordance to international standards with the engagement of communities as well as effective airports’ management as part of the policy planning process for national airports sustainability will be discussed. The methodological approaches of this paper includes philosophical, general scientific and special judicial methods. Results: national airport development planning policies must comply with the requirements of the high-level environmental assessment principles, which improve the ability to apply a consistent approach to the environmental impact of ground-based operations at the airport. International principles and standards to environmental protection from airport’s main negative impacts have to be studied for further implementation into national legislation, public policy and civil society’s consciousness for the purpose of practical application by airport’s management. Discussion: Strategic Objectives of International Civil Aviation Organization on environmental protection concerns; some of the main environmental and sustainable development concerns raised with respect to the operation of airports are emissions, noise issues, land use by airports, energy consumption, wastes.